Wyciszana klęska unii lubelskiej: litewska odsiecz wiedeńska - Obremski, Krzysztof (Tematy i Konteksty, 2019)
Did the Union of Lublin pass the test of time in 1683 in perhaps in the most difficult period for it? The Lithuanian relief of Vienna was only simulated, but if everything was calmed down, it was because the anti-Royal opposition was strong and John III was weak. At the same time, a problem arose of how to proclaim the glory of the Viennese triumph without humiliating the late and infamous Lithuania? The answer is a school Jesuit theatre and a performance entitled Picture of Victory [...].